Predictors of Changes in Medication Adherence in Blacks with Hypertension: Moving Beyond Cross-Sectional Data. Issue 5 (4th March 2016) - Schoenthaler, Antoinette M.; Butler, Mark; Chaplin, William; Tobin, Jonathan; Ogedegbe, Gbenga
Abstract: Background: Many studies have examined the multiple correlates of non-adherence in Blacks. However, they are largely cross-sectional; thus, these studies are unable to examine their predictive value on long-term medication adherence. Purpose: The purpose of this study is to examine the predictive role of key psychosocial and interpersonal factors on changes in medication adherence over a 1-year period. Methods: Data were collected from 815 Black patients with hypertension followed in community health centers. Hypothesized predictor variables included self-efficacy, depressive symptoms, social support, and patient-provider communication measured at baseline, 6, and 12 months. The dependent variable, medication adherence was assessed at baseline, 6, and 12 months. Latent Growth Modeling was used to evaluate the pathways between the latent predictor variables and medication adherence. Results: Participants were mostly female, low-income, with high school education or less, and mean age of 57 years. At baseline, high self-efficacy was associated with low depressive symptoms ( β = −0.22, p = 0.05), collaborative patient-provider communication ( β = 0.17, p = 0.006), and better medication adherence ( β = 1.04, p < 0.001). More social support and collaborative patient-provider communication were associated with low depressive symptoms ( β = −0.08, p = 0.02; β = −0.18, p = 0.01). More social support was positively associated with collaborative patient-provider communication ( β = 0.32, p < 0.001). In the longitudinal model, increasing self-efficacy over time predicted improvements in medication adherence 1 year later ( β = 1.76, p < 0.001; CFI = 0.95; RMSEA = 0.04; SRMR = 0.04; Chi-Squared Index of Model Fit = 1128.54). Conclusions: Self-efficacy is a key predictor of medication adherence over time in Black patients with hypertension. Initial levels of self-efficacy are influenced by the presence of depressive symptoms as well as the perceived quality of patient-provider communication.